The Regulatory Relationships Between the Gonad-Inhibiting Hormone and Insulin-Like Androgenic Gland Hormone-Binding Protein Genes in the Eyestalk-Androgenic Gland-Testis Axis of Macrobrachium rosenbergii - Tang, Meizhen; Lu, Zhijie; Babu, Sarath V; Yang, Guang; Li, Yanan; Xu, Zizheng; Pan, Gan; Qin, Zhendong; Lin, Li (Frontiers in Marine Science, 2021)
Gonad-inhibiting hormone (GIH) belongs to a family of neuropeptides that are released from the eyestalks of male crustaceans and plays key roles in gonadal maturity, reproduction, and molting. However, the detailed mechanisms underlying the effects of GIH on sexual regulation have yet to be elucidated. In the present study, we aimed to demonstrate how GIH mediate the activity of the androgenic gland (AG) to affect sexual regulation. To do this, we cloned and characterized a GIH sequence from Macrobrachium rosenbergii (MrGIH). The open reading frame (ORF) of MrGIH was 360 bp and codes for a polypeptide of 119 amino acids and a putative protein of 13.56 KDa. Tissue analysis showed that MrGIH is widely expressed in a range of tissues but particularly, the eyestalk, intestine, and nerve cord. Following the dsRNA silencing of MrGIH for 24 h, the expression levels of MrGIH were down-regulated in both the eyestalk and AG when compared with the negative control, but significantly increased the expression of Macrobrachium rosenbergii insulin-like androgenic gland hormone-binding protein (MrIAGBP) in AG, thus suggesting that MrGIH is an inhibitory factor for MrIAGBP. In addition, we found that eyestalk removal on certain days led to increased expression levels of MrIAGBP expression. The expression levels of MrIAGBP peaked at 2 d in the AG after unilateral and bilateral eyestalk ablation, exhibiting a 7.27- and 6.03-fold increase, respectively. Afterward, the expression of GIH protein levels were down-regulated and IAGBP protein levels were up-regulated after GIH silencing using immunohistochemistry method, combined with the increase of IAGBP protein levels after eyestalk ablation, confirming that MrGIH is an inhibitory factor that can moderately regulate AG development and IAGBP expression. Collectively, our findings enriched the mechanisms that control the sexual regulation pathway of male M. rosenbergii, and provided significant information for further explorations of the mechanism underlying sex regulation in other decapod crustaceans.